2022
DOI: 10.3390/ijerph192215369
|View full text |Cite
|
Sign up to set email alerts
|

Partnership between Chinese Dance Sport Couples: A Consensual Qualitative Research Analysis

Abstract: The aim of our study was to explore the conceptions related to partnership between dance sport couples. We conducted in-depth interviews with 20 registered athletes of the Chinese Dance Sports Federation (CDSF) about partnership between dance couples, using the Consensual Qualitative Research (CQR) method. Results revealed that partnership tended to stem from seven domains: (1) mutual understanding, (2) instant intimacy, (3) long-term affection, (4) obligational ties, (5) instrumental ties, (6) tacit factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Obligatory instrumental ties (OIT) refer to the reciprocal behavior tendency of elite dancer couples based on the principle of obligation ruled by "renqing" to maintain their partnership during the whole process of taking DanceSport competition as the goal. It includes the obligation and instrument factors (Liu et al, 2022). First, because the importance of effective talent development in sports is well established as a key aspect of achieving high-level performance (Taylor et al, 2022), the competitive victory in DanceSport is taken as the starting point (Bednarzowa and Młodzikowska, 1983;Budnik-Przybylska et al, 2015).…”
Section: Dancesport Partnership In Our Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Obligatory instrumental ties (OIT) refer to the reciprocal behavior tendency of elite dancer couples based on the principle of obligation ruled by "renqing" to maintain their partnership during the whole process of taking DanceSport competition as the goal. It includes the obligation and instrument factors (Liu et al, 2022). First, because the importance of effective talent development in sports is well established as a key aspect of achieving high-level performance (Taylor et al, 2022), the competitive victory in DanceSport is taken as the starting point (Bednarzowa and Młodzikowska, 1983;Budnik-Przybylska et al, 2015).…”
Section: Dancesport Partnership In Our Studymentioning
confidence: 99%
“…In addition, according to Chen et al (2013), the analysis of the characteristics of Chinese "guanxi (interpersonal relationship) will always be considered as a capital, " as it can be found that the DanceSport partnership is a tool to achieve goals. Therefore, partners often exhibit a high degree of reciprocity and interaction (Reisman, 1981;Marion, 2006), and partnership is always taken as an instrument to obtain benefits (Lai, 2014;Liu et al, 2022).…”
Section: Dancesport Partnership In Our Studymentioning
confidence: 99%
See 3 more Smart Citations